(untitled) (Cadernos de Sociomuseologia, 2018)
This article proposes management strategies for museological community initiatives based on participation and territorial identity as key factors to these initiatives and mobilizers of their organizational and inter-organizational dimension. The organizational mobilization starts from the organization’s understanding as a process that seeks to connect the ‘functional areas’ of the museum (linked, specifically, to museological functions) to the ‘managerial areas’ (related to management activities) by developing action strategies on internal museum context, enabling a more complete and managerial vision of the organization. The inter-organizational mobilization refers to the potential for external relationships, either through partnerships or a networking, but also through the cooperation between organizations that share the territorial identity and the dynamics of participation. From the qualitative approach, document analysis and studies of different museums, national and international ones, the research outcomes (management strategies), with technological vocation, helps community leaders, social managers and cultural entrepreneurs of communities to better manage museums based on community participation and territorial. It also helps in the training for social museology and management. Consequently, it becomes relevant for guiding public policies in relation to the role of the management in the development of community-based museums. Keywords: community museum management; organization; interorganizations; participation; territorial identity.